The social stress of publichealth emergencies among medical practitioners (One Health & Risk Management, 2021)
Introduction. One of the greatest states of emergency is the coronavirus pandemic (COVID-19) announced by the World Health Organization on 30 January 2020. Even though each pandemic has differences in regional, geographic and pathogenic characteristics and mortality rates, studies suggest that pandemics have a negative impact on healthy people. As a result of the rapid spread and increased mortality rate, this state of emergency has caused public health problems worldwide. In addition, the stress experienced by people in response to this situation has also had a severe negative effect on health professionals. The purpose of the requirement is to analyze the stress conditions of medical practitioners during public health emergencies.Material and methods. Research of the selected bibliographic sources in PubMed has allowed this study to be carried out. The words used in the search engine were: "Health professionals", "stress" and "pandemic". The 12 latest sources were selected. Results. In the last 10 years, several States of public health emergency have been recorded (COVID 19 pandemic, the Paris terrorist attack, the Nepal earthquake, the Zika outbreak, the Ebola outbreak, the poliomyelitis). The COVID-19 pandemic has created a multitude of acute challenges for healthcare institutions, including overloading of medical practitioners, lack of supply of necessary seafarers, the need to redesign care and financial losses.Stressful events, such as emergency conditions, can increase anxiety. Health workers in a variety of areas, exposure risks report anxiety, depression, suffering and insomnia during the COVID-19 pandemic. Jackson et al. (2020) affirms that nurses, who are mentally, emotionally, and spiritually strong, play a critical role both in preventing the transmission of infections and in medical care of patients during global pandemics. Compared to emergency workers, health workers had higher stress levels, leading them to more severe stress and difficulties in teamwork, physical fatigue, somatic diseases, irritability and difficulties in maintaining control of the situation, in taking decisions and predicting the consequences of their actions.Major risk factors in developing stress and mental problems related to the COVID-19 pandemic according to Kisely et al. Are: beginner physicians, period of exposure, long quarantine time, having an infected family member, lack of practical support, stigmatization, and young age. Brier et al. (2020) supplemented the list with: Fear of their health, working conditions inappropriate to the situation, lack of protective equipment and means of aid. For health workers, social support reduces occupational stress and prevents common psychological suffering and psychiatric symptoms. Colleagues' support is also significant for health workers, as it impacts on work efficiency. Conclusions. Stress together with depression can lead to the development of BURNOUT syndrome, which affects the health of medical practitioners but also the result of work. Thus, proper management of emergency States is required both at the institution level and at the level of the ministry and the government.
Keywords: state of emergency; stress; medical practitioners; COVID-19.